IMPLEMENTATION OF THE QUESTION AND ANSWER METHOD IN LEARNING SOCIAL SCIENCES IN PRIMARY SCHOOLS - Putu Satya Narayanti (Indonesian Journal of Education (INJOE), 2023)
This literature review explains the implementation of the question and answer method in social science learning in elementary schools. The question and answer method is a teaching method that allows dialogue between the teacher and students, the teacher asks and the students answer or vice versa, the students ask and the teacher answers. In social studies learning, it is hoped that students will not only be able to master social studies theories in social life, but also be able to live real life in society as social people in an adult and wise manner, therefore the question and answer method is one method that is suitable to be applied. By implementing the question and answer method in teaching and learning, it is hoped that there will be reciprocity between teachers and students. The class atmosphere will be looser than teaching that uses the lecture method. Students have had the opportunity to participate, although it is still very limited. However, class conditions appear to be more lively and the subject matter discussed is developing more dynamically, because the teacher and students are both active, students are given the opportunity to express their opinions related to the subject of discussion.